Student Counselors' Moral, Intellectual, and Professional Ethical Identity Development. Issue 1 (April 2017) - Lloyd‐Hazlett, Jessica; Foster, Victoria A.
Abstract : Professional identity is characterized by the integration of individuals' professional and personal selves. The authors used a multiple regression design to examine counselor professional ethical identity development, with specific attention to moral and intellectual development. Student counselors ( N = 59) completed the Modified Subject‐Object Interview (Monson & Hamilton, 2010 ), Defining Issues Test–2 (Rest, Narvaez, Bebeau, & Thoma, 1999a ), and Learning Environment Preferences scale (Moore, 1987 ). Moral development was the most significant predictor of professional ethical identity development. Preparatory and research strategies to enhance professional ethical identity formation are discussed.